ANALISIS KONTEKS WACANA DALAM RUBRIK HUKUM DAN KRIMINAL PADA PORTAL BERITA CNN INDONESIA - Pamungkas, Catur Setiawan; Alber, Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This study aims to describe, analyze and interpret the context of discourse in the law and criminal rubric on the CNN Indonesia news portal. The context of the discourse is formed from various elements, namely the setting (setting and scene), participants, results (ends), messages, ways (keys), means (instruments) and norms. The problem in this research is what is the context of written discourse in the law and criminal rubric on the CNN Indonesia news portal? The theory used in this study is Hymes' theory in Djajasudarma (2017) and other supporting theories. The method used is descriptive method. The data collection technique used is the documentation technique. The data analysis technique used is content analysis technique. The results of the analysis of the discourse context in the law and criminal rubric on the CNN Indonesia news portal are in the form of background elements (settings and scenes) that refer to different places and times from all over Indonesia, including Aceh, Jakarta, Yogyakarta, Makassar, Solo, East Nusa Tenggara and etc., participants involved from the whole discourse there are 92 participants, the results (ends) in the discourse aim to provide information on law and criminal events, the occurrence of criminal acts, provide the results of court decisions and so on, the message, namely giving different messages or messages from each of them not to commit criminal acts, to be more careful with crime acts and so on, the way (key) is conveyed in a convincing, blazing, firm and demanding way, means (instrument) using written language, norms namely lectures and discussions, type (genre) namely CNN Indonesia news portal.